Internet of things: Conceptual network structure, main challenges and future directions - Leonardo B. Furstenau; Yan Pablo Reckziegel Rodrigues; Michele Kremer Sott; Pedro Leivas; Michael S. Dohan; José Ricardo López-Robles; Manuel J. Cobo; Nicola Luigi Bragazzi; Kim-Kwang Raymond Choo (Digital Communications and Networks, 2023)
Internet of Things (IoT) is a key technology trend that supports our digitalized society in applications such as smart countries and smart cities. In this study, we investigate the existing strategic themes, thematic evolution structure, key challenges, and potential research opportunities associated with the IoT. For this study, we conduct a Bibliometric Performance and Network Analysis (BPNA), supplemented by an exhaustive Systematic Literature Review (SLR). Specifically, in BPNA, the software SciMAT is used to analyze 14,385 documents and 30,381 keywords in the Web of Science (WoS) database, which was released between 2002 and 2019. The results reveal that 31 clusters are classified according to their importance and development, and the conceptual structures of key clusters are presented, along with their performance analysis and the relationship with other subthemes. The thematic evolution structure describes the important cluster(s) over time. For the SLR, 23 documents are analyzed. The SLR reveals key challenges and limitations associated with the IoT. We expect the results will form the basis of future research and guide decision-making in the IoT and other supporting industries.